INFLUENCE OF FREE DRAWINGS TO IMPROVE CREATIVITY IN 5TH GRADER CHILDREN IN MI MU'AWANAH AL-HASYIMIYAH - siti indatul laili; enny virda Yuniarti (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2017)
Free drawing on children provides a vast opportunity to explore in order to fulfill curiosity. By drawing the child freely express his ideas through fantasy. Safety and freedom are important conditions for the growth of creativity. The objective of the study was to prove the effect of free drawing on the improvement of creativity in 5th grader children in MI Mu'awanah Al-Hasyimiyah. This research design used one group pre-posttest design. The population of this research were all 5th graders in MI Mu'awanah Al-Hasyimiyah as many as 26 children. The sample of this research was all 5th graders in MI Mu'awanah Al-Hasyimiyah as many as 26 children taken with total sampling. Measurement tool used by the questionnaire to assess creativity. Research was on 15th â€“ 27thJuly 2017. Statistic test used Wilcoxon Sign Rank Test. The results showed that all 26 (100%) of respondents had positive creativity and Ïcount 0,014 = and a table = 0,05. It meant that there was a free drawing effect on the increase of creativity in 5th grader children in MI Mu'awanah Al-Hasyimiyah. When a child draws, the child will perform activities of crossing out, scratching, and color freely. Thus, able to create various ideas and will give satisfaction for children. New ideas as pieces of creative thinking for children. Keywords: child, creativity, free drawing